2022
DOI: 10.1002/cjp2.272
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive uveal melanoma displays a high degree of centrosome amplification, opening the door to therapeutic intervention

Abstract: Uveal melanoma (UM) is the most common intraocular cancer in adults. Whilst treatment of primary UM (PUM) is often successful, around 50% of patients develop metastatic disease with poor outcomes, linked to chromosome 3 loss (monosomy 3, M3). Advances in understanding UM cell biology may indicate new therapeutic options. We report that UM exhibits centrosome abnormalities, which in other cancers are associated with increased invasiveness and worse prognosis, but also represent a potential Achilles' heel for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…Liu et al . also reported that KIFC1 was overexpressed in NSCLC compared to non-malignant lung tissues and that high expression was associated with worse prognosis, which is consistent with findings from other LC studies[3537, 59, 60] and reports in other malignancies[34, 36, 6165]. Our analyses of multiple LC cohorts confirmed associations of KIFC1 with clinical factors including survival and stage as well as CA20.…”
Section: Discussionsupporting
confidence: 91%
“…Liu et al . also reported that KIFC1 was overexpressed in NSCLC compared to non-malignant lung tissues and that high expression was associated with worse prognosis, which is consistent with findings from other LC studies[3537, 59, 60] and reports in other malignancies[34, 36, 6165]. Our analyses of multiple LC cohorts confirmed associations of KIFC1 with clinical factors including survival and stage as well as CA20.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, loss of 9p21 – where CDKN2A/B reside - is prevalent in melanoma and has recently been associated with primary resistance to ICI treatment ( 99 ). Finally, a recent study ( 82 ) utilizing a cohort of 75 primary uveal melanomas showed amplified centrosome numbers as well as an increase in centrosomes with enlarged pericentriolar matrix (PCM) relative to the surrounding normal tissue, with PCM phenotype significantly associated with monosomy of chromosome 3. Uveal melanomas with monosomy of chromosome 3 have increased aneuploidy compared to those with disomy of the same chromosome, in agreement with a scenario of increased centrosomal abnormalities in the former group ( 82 ).…”
Section: Mechanisms That Lead To Aneuploidymentioning
confidence: 99%
“…Finally, a recent study (82) utilizing a cohort of 75 primary uveal melanomas showed amplified centrosome numbers as well as an increase in centrosomes with enlarged pericentriolar matrix (PCM) relative to the surrounding normal tissue, with PCM phenotype significantly associated with monosomy of chromosome 3. Uveal melanomas with monosomy of chromosome 3 have increased aneuploidy compared to those with disomy of the same chromosome, in agreement with a scenario of increased centrosomal abnormalities in the former group (82). The authors argue that prior observations that melanomas with monosomy of chromosome 3 have increased aneuploidy compared to melanomas with disomy of this chromosome ( 66) is consistent with increased centrosomal abnormalities in the former melanoma group.…”
Section: Centrosomal Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, CA has been reported for the first time in UVM. Sabat-Pośpiech et al confirmed that CA existed in UVM primary tumors and cell lines ( 13 ). Moreover, a study showed that chromosome monosomy 3 (M3) and BAP1 mutant UVM had a higher level of CA, which was related to worse prognosis ( 13 ); however, this is the only study available on the role of CA in UVM and the mechanism needs further detailed study.…”
Section: Introductionmentioning
confidence: 96%